High resolution nanomechanical characterization of multi‐domain model membranes by fast Force Volume†. Issue 12 (29th July 2015) - Seghezza, Silvia; Dante, Silvia; Diaspro, Alberto; Canale, Claudio
Abstract : Plasma membrane is a complex structure, mainly composed by lipids and proteins, which plays a pivotal role in cell metabolism by regulating its selective permeability to ions and molecules. According to the "raft hypothesis", lipids in the bilayer are not forming a structurally passive solvent, but are rather organized in specific domains, which present different structural and functional characteristics. The mechanical properties of the lipid part of plasma membrane have been recently characterized through Atomic Force Microscopy, by analyzing the features of force vs distance curves collected on supported lipid bilayers (SLBs). In case of lipid domains sizing from tens to hundreds of nanometers, which mimic in a good way the lateral organization of real membranes, a high lateral resolution and a large number of curves are often required for properly expressing the complexity of the system, with a consequent exponential growth of acquisition and processing time. In this paper we propose a method, based on a recently developed high speed Force Volume technique and on home‐built data processing software, for the mechanical characterization of nanostructured SLBs. With our software we have been able to process data set composed by tens of thousands of curves, collected with a spatial resolution ranging from 8 to 40 nm/pixel. Multiparametric maps and distribution histograms produced by our analysis allowed identifying a specific behavior for each lipid phase in the investigated model membranes, even in presence of nanosized features. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : High‐speed Force Volume approach was used to collect force–distance curves on nanostructured phase‐separating model membranes. Mechanical information were extracted from each curve through home‐built software, and remapped according to the topography. Using this approach, distinct distributions of values, describing the considered parameters, could be identified for each lipid phase.